1997
DOI: 10.1148/radiology.203.3.9169713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an on-line patient exposure meter in neuroradiology.

Abstract: An on-line patient exposure meter can provide accurate radiation skin dose data in patients undergoing diagnostic and therapeutic neuroradiologic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…Although there have been several reports analyzing a patient's skin dose in neurointerventional procedures, [1][2][3][4][5][11][12][13][14][15][16][17][18] there are few reports that could demonstrate the regional distribution of skin dose. 5,6,19,20 In this study, we demonstrated that the ESD on the area that encompasses the right temporal and occipital region was considerably higher than that on the frontal region.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several reports analyzing a patient's skin dose in neurointerventional procedures, [1][2][3][4][5][11][12][13][14][15][16][17][18] there are few reports that could demonstrate the regional distribution of skin dose. 5,6,19,20 In this study, we demonstrated that the ESD on the area that encompasses the right temporal and occipital region was considerably higher than that on the frontal region.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods for patient dosimetry in IR have been proposed and tested [22,23,24,25,26,27,28,29]. Basically, all the methods try to obtain the skin dose distribution with different approaches: arrays of TLD dosimeters; slow radiographic films (with the problem of saturation at 1.0-1.5 Gy); radiochromic films (without saturation at several Gy but still expensive and difficult to calibrate and to process); and on-line software, which was offered by Siemens but now is off the market [30].…”
Section: Patient Dosimetry Methodsmentioning
confidence: 99%
“…Gkanatsios et al (1997) recently have demonstrated the accuracy of an on-line patient exposure meter in the determination of skin doses. This meter does not measure radiation directly.…”
Section: Introductionmentioning
confidence: 99%